Differentiated service provisioning in the MAC layer of cognitive radio mesh networks. (1st January 2012) - How, Kiam Cheng; Ma, Maode; Qin, Yang
MAC protocols utilising the enhanced distributed channel access in IEEE 802.11-2007 can provide differentiated QoS in wireless networks. However, the performance of high priority traffic can be seriously degraded in the presence of strong noise over the wireless channels. Schemes utilising adaptive modulation and coding technique have also been proposed for QoS provisioning. They can provide limited protection in the presence of noise but are ineffective in a high noise scenario. Although multiple non-overlapped channels exist in the 2.4 GHz and 5 GHz spectrum, most IEEE 802.11-based multi-hop ad hoc networks today use only a single channel at anytime and cannot fully exploit the aggregate bandwidth available in the radio spectrum. By identifying vacant channels through the use of cognitive radios technique, the noise problem can be mitigated by distributing network traffic across multiple vacant channels to reduce the node density per transmission channel. In this paper, we propose the MAC-layer QoS provisioning protocol which combines adaptive modulation and coding with dynamic spectrum access. Simulation results demonstrate that MQPP can achieve better performance in terms of lower delay and higher throughput.